Head injury in asylum seekers and refugees referred with psychological trauma. (3rd October 2016) - Doherty, S. M.; Craig, R.; Gardani, M.; McMillan, T. M.
Abstract : Objective: Individuals who seek asylum are frequently fleeing violent persecution and may experience head injury (HI). However, little is known about the prevalence of HI in asylum seekers and refugees (ASR) despite the potential for HI to significantly affect cognitive and emotional functioning and to compromise asylum outcomes. This preliminary study investigates the prevalence of HI in ASR referred to a complex psychological trauma service. Method: Participants were 115 adult ASR referred to a community psychological trauma service with moderate to severe mental health problems associated with psychological trauma. They were screened for a history of HI using a questionnaire developed for the study. Interpreters were used when required. Results: The overall prevalence of HI was 51%. At least 38% of those with HI had a moderate–severe HI that could cause persisting disability. In 53% of those with HI, the cause was torture, human trafficking or domestic violence. Repeat HI can have cumulative effects on function; it was common, and was reported in 68% of those with HI. An injury to the head was not known to mental health clinicians prior to screening in 64% of cases. Conclusion: The emotional and cognitive consequences of HI in ASR may increase the vulnerability of this disadvantaged group, and can be associated with neurobehavioural problems affecting daily life and may compromise asylum outcomes. Routine screening for HI in ASR is needed, as are links to neuropsychology and brain injury services for advice, assessment and intervention.